Frequency of Urological Carcinomas in Patients with Gross Haematuria - Muzzamil Riaz Malik, Amjad Saleem, Yassar Hussain Patujo, Shaheer Ahmad Khan, Abdullah, Sikandar Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the frequency of urological carcinomas in patients with gross haematuria. Study Design: Prospective study Place and Duration : Department of Urology, PIMS Islamabad, from December, 2021 to May, 2022. Methods: There were one hundred and forty five patients with ages 20-55 years were presented in this study. All the included patients had blood in urine. After receiving informed written permission, detailed demographic information about the recruited patients, including age, gender, body mass index, and causes of haematuria, was compiled. Urine cytology and microscopy were used to rule out the presence of malignant cells in haematuria. Every time a cystoscopy or computed tomography (CT) scan was needed to monitor the health of our patients, we sent them for an ultrasound. Frequency of urological carcinomas was calculated. SPSS 22.0 was used to analyze all of the data in the study. Results: There were 90 (62.1%) males and 55 (37.9%) females in our study. Mean age of the patients was 41.8±5.54 years with mean BMI 24.5±4.76 kg/m2. 80 (55.2%) patients were literate. Most common cause was urinary tract infection found in 50 (34.5%) cases, trauma in 45 (31.03%), urolithiasis in 30 (20.7%) cases and smoking in 20 (13.8%) patients. Prevalence of urological carcinoma was found in 27 (18.6%) cases. Conclusion: We found a significant incidence of urological carcinomas in our research. Gross haematuria was most often caused by urinary tract infection or trauma. Keywords: Urological carcinomas, Gross haematuria, Urinary tract infection